Atonement and comparative theology : the cross in dialogue with other religions - Cornille, Catherine (New York : Fordham University Press, 2021)
"The central Christian belief in salvation through the suffering, death, and resurrection of Jesus Christ remains one of the most intractable mysteries of Christian faith. Throughout history, it has given rise to various theories of atonement, many of which have been subject to critique as they no longer speak to contemporary notions of evil and sin or to current conceptions of justice. One of the important challenges for contemporary Christian theology thus involves exploring new ways of understanding the salvific meaning of the cross. In Atonement and Comparative Theology, Christian theologians with expertise in Judaism, Islam, Hinduism, Buddhism, Daoism, and African Religions reflect on how engagement with these traditions sheds new light on the Christian understanding of atonement by pointing to analogous structures of sin and salvation, drawing attention to the scandal of the cross as seen by the religious other, and re-interpreting aspects of the Christian understanding of atonement. Together, they illustrate the possibilities for comparative theology to deepen and enrich Christian theological reflection"--
Why Atonement? -- Who needs it?: atonement in Muslim-Christian theological engagement / Daniel A. Madigan -- Christian atonement enlightened by a Buddhist perspective on craving / Thierry-Marie Courau -- How Q 5:75 can help Christians conceptualize atonement / Klaus von Stosch -- Not for myself alone : atonement and penance after Daoism / Bede Benjamin Bidlack -- Suffering and the Scandal of the Cross -- God's suffering in the Hindu-Christian gaze / Francis X. Clooney -- More than meets the eye : the cross as maṇ̣ḍ̜̣ala / Michelle Voss Roberts -- Divine suffering and covenantal belonging : considering the atonement with Heschel and Moltmann / Daniel Joslyn-Siemiatkoski -- Clash and continuity of interpretation of redemptive suffering between African religions and Christianity / Elochukwu Uzukwu -- Rethinking Redemption -- Redemptive suffering after the Shoah : going back and forth between Jewish and Christian traditions / Marianne Moyaert -- Judgment on the cross : resurrection as divine vindication / Joshua Ralston -- At one or not at one? : Christian atonement in light of Buddhist perspectives / Leo D. Lefebure -- How empty is the cross? : realization and novelty in stonement / S. Mark Heim.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Atonement; Christianity and other religions; Christianisme -- Relations; RELIGION -- Comparative Religion; Atonement; Christianity and other religions